Nickel (II) chloride schiff base complex: Synthesis, characterization, toxicity, antibacterial and leishmanicidal activity. (5th January 2022) - Maia, Danielle O.; Santos, Valdenice F.; Barbosa, Cristina R.S.; Fróes, Yuri N.; Muniz, Debora F.; Santos, Ana L.E.; Santos, Maria H.C.; Silva, Romério R.S.; Silva, Cláudio G.L.; Souza, Racquel O.S.; Sousa, Joicy C.S.; Coutinho, Henrique D.M.; et al.
Abstract: The use of schiff base complex against microbial agentes a has recently received more attention as a strategy to combat infections caused by multidrug-resistant bacteria and leishmania. This study aimed to evaluate the toxicity, antibacterial and leishmanicidal activities of the nickel (II) chloride schiff base complex ([Ni(L2)] against Leishmania amazonensis promastigote, multi-resistant bacterial strains and evaluate to modulate antibiotic activity against multi-resistant bacterial. The schiff base complex was characterized by the techniques of elemental analysis, Fourier transform infrared spectroscopy (FTIR), UV–vis absorption spectroscopy and thermal analysis (TGA/DTG/DSC). The [Ni(L2)] complex presented moderate toxicity in saline artemia (LC50  = 150.8 μg/mL). In leishmanicidal assay, the NiL2 complex showed values of IC50 of (6.079 μg/mL ± 0.05656 at the 24 h), (0.854 μg/mL ± 0.02474, 48 h) and (1.076 μg/mL ± 0.04039, 72 h). In antibacterial assay, the [Ni(L2)] complex presented significant inhibited the bacterial growth of P. aeruginosa (MIC = 256 μg/mL). However, [Ni(L2)] complex did not present clinically relevant minimum inhibitory concentration (MIC ≥1024 μg/mL) against S. aureus and E. coli . The combination of [Ni(L2)] complex and antibacterial drugs resulted in the increased antibiotic activity of gentamicin and amikacin against S. aureus and E.coli multi-resistant strains. Thus, our results showed that [Ni(L2)] complex is a promising molecule for the development of new therapies associated with aminoglycoside antibiotics and in disease control related to resistant bacteria and leishmaniasis. Highlights: [Ni(L2)] complex inhibits the growth of Pseudomonas aeruginosa . [Ni(L2)] complex increases the activity of antibiotics against multiresistant bacteria. [Ni(L2)] complex presented moderate toxicity in saline artemia. [Ni(L2)] complex inhibits the growth of Leishmania infantum .